Automatic procedure for selecting flood events and identifying flood characteristics from daily streamflow data. (November 2021) - Zhang, Qin; Zhang, Liping; She, Dunxian; Wang, Shuxia; Wang, Gangsheng; Zeng, Sidong
Abstract: The selection of flood events and determination of flood characteristics (e.g. start and end dates, peak discharge, volume, and duration) are the first critical steps for flood analyses. To obtain the key flood information accurately, we used the automatic peak over threshold (POT) model for flood sampling and proposed an automatic approach to determine flood characteristics using the master recession curve analysis (MRC) method. We further developed a graphical user interface (GUI) and toolbox for this procedure in MATLAB. Model parameter estimation experiment (MOPEX) data from 423 stations were used to evaluate the proposed method. Our results suggest that the proposed procedure performs well for watersheds with diverse characteristics. The developed toolbox can be conveniently applied to other watersheds for flood sampling and the characterisation of flood events, thus helping reduce the uncertainty in subsequent flood analyses, such as multivariable flood frequency and trend analyses. Graphical abstract: Image 1 Highlights: We propose a generic standardized method for identifying the flood characteristics. An automatic procedure to select flood events and identify flood characteristics is constructed. We developed a graphical user interface (GUI) for this automatic procedure in MATLAB. The validation results show that our method has good applicability to watersheds with diverse characteristics.